Transparency of regulation and cross-border bank mergers - Matthias Köhler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
There is ample anecdotal evidence that political influence constitutes a barrier to the integration of the EU banking market. Based on a dataset on the transparency on the supervisory review process of bank mergers in the EU, I estimate the probability that a bank is taken over as a function of bank and country characteristics and the transparency of merger control. The results indicate that banks are systematically more likely to be taken over by foreign credit institutions if the regulatory process is transparent. Particularly large banks seem to be less likely to be taken over by foreign banks if merger control lacks transparency.
Older version: http://hdl.handle.net/10419/24679
Keywords: 330; Mergers and acquisitions; banks; barriers to consolidation; political interference; Fusionskontrolle; Internationale Bank; Übernahme; Fusion; EU-Staaten